Les défis de l’assurance I.A.R.D. - Parizeau, Robert (Assurances)

(untitled) (HEC Montréal, 1987)
Discussing the challenges of the Property and Casualty insurance industry in 1986 is in itself a challenge. Indeed, the insurance industry is currently undergoint major changes. Whether a broker or an insurer, it is difficult for anyone to give an accurate prediction of the market's evolution in Canada over the next few years. In an attempt to pinpoint some of the major problems which we may face in the future, the author has provided a brief retrospective of our industry. Mr. Parizeau examines the insurer and insurance broker concentration and the evolution of the reinsurance market; he concludes with a look at some aspects of the relationship between the industry and Government authorities.